How did labor markets work in lancashire? more evidence on prices and quantities in cotton spinning, 1822–1852 - Huberman, Michael (Explorations in Economic History, 1991)
Using yarn prices and output as proxies for wages and employment, this paper asks how cotton spinning firms in the heyday of industrialization responded to demand shocks. The evidence is consistent with a two-sector efficiency wage model composed of large and small firms. Large firms incurred monitoring costs on their new technology. To eliminate shirking, they paid efficiency wages and laid off workers when faced by a reduction in demand. In small firms technical change was slower, and since monitoring was not a problem, they cut wages. Over the period, the number of small firms declined and layoffs increased.